Identifikasi Nilai Skala Vertikal pada Interpolasi Fractal yang Memaksimalkan Kualitas Citra Hasil Perbesaran - Maryanto, Eddy (JUITA: Jurnal Informatika, 2016)
The aim of this research is to investigate the effect of vertical scale value of fractal interpolation to the quality of magnified image resulted. In this research, three groups of rgb image are used, they are of bird, tree, and batik images. The results of the research show that vertical scale value of zero gives the best quality magnified image. The farther the vertical scale value from zero, the worse the quality of the magnified image